Analysis of Parameters for Fatty Acid Methyl Esters Production from Refined Palm Oil for Use as Biodiesel in the Single- and Two-stage Processes - Ilham, Zul (Faculty of Medicine, UM, 2009)
In the present study, the production of fatty acid methyl esters (FAME) for use as biodiesel from the alkaline transesterification of refined palm oil (RPO) was found to occur optimally using a molar RPO (triglyceride) to methanol ratio of 1:6, in the presence of 1% NaOH (catalyst) in methanol (w/v), at 60ºC, in 30 min and with vigorous mixing. Comparing performance of the reaction that was carried out in the single- and two-stage processes showed that the single-stage process was more superior to the latter as it was faster, easier, required less handling procedure and produced higher yield of FAME. Under the optimally derived conditions, the single-stage process proved capable of more than 95% yield of FAME. When analyzed, the RPO FAME produced met the standards for use as biodiesel in five basic properties tested.